Integrative analyses unveil speciation linked to host plant shift in Spialia butterflies - Hernández-Roldán, Juan L; Dapporto, Leonardo; Dincă, Vlad; Vicente, Juan C; Hornett, Emily A; Šíchová, Jindra; Lukhtanov, Vladimir A; Talavera, Gerard; Vila, Roger (Molecular ecology, 2016)
Discovering cryptic species in well-studied areas and taxonomic groups can have profound implications in understanding eco-evolutionary processes and in nature conservation because such groups often involve research models and act as flagship taxa for nature management. In this study, we use an array of techniques to study the butterflies in the Spialia sertorius species group (Lepidoptera, Hesperiidae). The integration of genetic, chemical, cytogenetic, morphological, ecological and microbiological data indicates that the sertorius species complex includes at least five species that differentiated during the last three million years. As a result, we propose the restitution of the species status for two taxa often treated as subspecies, Spialia ali (Oberthür, 1881) stat. rest. and Spialia therapne (Rambur, 1832) stat. rest., and describe a new cryptic species Spialia rosae Hernández-Roldán, Dapporto, Dincă, Vicente & Vila sp. nov. Spialia sertorius (Hoffmannsegg, 1804) and S. rosae are sympatric and synmorphic, but show constant differences in mitochondrial DNA, chemical profiles and ecology, suggesting that S. rosae represents a case of ecological speciation involving larval host plant and altitudinal shift, and apparently associated with Wolbachia infection. This study exemplifies how a multidisciplinary approach can reveal elusive cases of hidden diversity.
Keywords: Animals; Butterflies; Genetic Speciation; DNA, Mitochondrial; Wolbachia; Altitude; východní Evropa; Africa, Northern; nadmořská výška; Phylogeny; Europe, Eastern; mitochondriální DNA; motýli; vznik druhů (genetika); Larva; zvířata; severní Afrika; fylogeneze; larva